Mothers' Needs in Managing Stunting among Under-Two Children: A Qualitative Study in Surakarta City - Ika Sumiyarsi Sukamto; Septiana Juwita (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Background: Although the government has implemented various interventions, stunting remains a serious public health issue in Indonesia. This condition calls for a new understanding, particularly from the perspective of mothers with stunted children. Objective: This study aims to explore the mothers’ needs managing stunting under-two children in Surakarta City.Method: A qualitative was employed through focus group discussions (FGDs). A total of 20 informants aged 24–50 years were selected as participants. They resided in Surakarta City and were divided into two groups: the first group consisted of four nutritionists from health facilities and six health cadres, while the second group included ten mothers of stunted children. Data were analysed using Colaizzi’s method and managed with Nvivo software.Result: The study revealed five main themes related to mothers’ needs: (1) societal perceptions of stunting, (2) program availability, (3) barriers to program implementation, (4) expected prevention efforts, and (5) stunting management requirements. These findings indicate that mothers of stunted children require a deeper understanding of effective stunting management strategies and access to affordable nutritional resources to support their children’s physical growth and cognitive development.Conclusion: Social support from the community, easy access to information, and education on healthy eating patterns and stunting prevention are crucial aspects. Mothers with stunted children need adequate information on proper stunting management and access to affordable nutrition. Furthermore, community support and the availability of easily understandable information, including through audio-visual media, play a significant role in stunting prevention and management.